The moral and political economy of suicide prevention. (March 2022) - Fitzpatrick, Scott J
Suicide prevention occurs within a web of social, moral, and political relations that are acknowledged, yet rarely made explicit. In this work, I analyse these interrelations using concepts of moral and political economy to demonstrate how moral norms and values interconnect with political and economic systems to inform the way suicide prevention is structured, legitimated, and enacted. Suicide prevention is replete with ideologies of individualism, risk, and economic rationalism that translate into a specific set of social practices. These bring a number of ethical, procedural, and distributive considerations to the fore. Closer attention to these issues is needed to reflect the moral and political contexts in which decision-making about suicide prevention occurs, and the implications of these decisions for policy, practice, and for those whose lives they impact.